Helping Indigenous students at First Nations University of Canada to thrive ... - Bighead, Lisa (My University, 2019)
This thesis researched what makes Indigenous students thrive at FNUniv. The focus was specifically on the student perspective. This action research inquiry was led by an Indigenous methodology and complimented with an appreciative inquiry approach. Using interviews and a group discussion that incorporated Photovoice, common themes were identified to help identify what Indigenous students felt made them thrive through their studies. The literature review focused on student success and persistence and honed in on research specific to Indigenous populations. From the research conducted, a collective of themes was identified and used as the basis for four recommendations. In addition, an overarching recommendation was made that linked to the Cree medicine wheel teachings and tipi teachings to offer a model for Indigenous student thriving. ...